(untitled) (Global Journal of Medical Research, 2018)
Ejaculation capabilities and semen characteristics depending on seasonal variations are presented in this paper. The mean temperature range in the study area was 25.6°C (February) -30.5°C (May) and the mean humidity range was correspondingly between 62.5-80.4% (February) and 77.6-83.3% (May). The photoperiod was minimum in February (13h/day) and maximum in May (15.6h/day). Out of 927 collection attempts, 509 attempts ended with successful ejaculation and hence the semen collection rate was 54.9±8.8%. The highest ejaculation rate was 65% in March followed by 63.7% in November, whereas it was low (44.7%) in September. Average volume of semen ejaculated from a bird in one collection was 9.3±1.5µl and the range was 6.1 ± 0.2 µl (September) -10.8 ± 0.7 µl (November)/ collection (p>0.05). The average semen concentration was 4.01±0.5×10 9 /ml.